1986
DOI: 10.1152/ajpgi.1986.251.5.g674
|View full text |Cite
|
Sign up to set email alerts
|

Role of glucagon in splanchnic hyperemia of chronic portal hypertension

Abstract: The role of glucagon as a blood-borne mediator of the hyperdynamic circulation associated with chronic portal venous hypertension was assessed in the rat portal vein stenosis model. Selective removal of pancreatic glucagon from the circulation was achieved by intravenous infusion of a highly specific glucagon antiserum. Blood flow to splanchnic organs, kidneys, and testicles was measured with radioactive microspheres, and the reference-sample method. Glucagon antiserum had no effect on blood flow in the gastro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
1
2

Year Published

1988
1988
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(44 citation statements)
references
References 0 publications
2
39
1
2
Order By: Relevance
“…Serum glucagon levels were significantly correlated with high systemic vascular resistance index (r = -0.523; P = 0) and HVPG (r = 0.34; P = 0.019). Glucagon significantly increases portal pressure [157][158][159] , and causes splanchnic vasodilation [148] . Geraghty et al [158] found a strong correlation between portal pressure and glucagon levels (r = 0.85).…”
Section: Angiogenesismentioning
confidence: 99%
“…Serum glucagon levels were significantly correlated with high systemic vascular resistance index (r = -0.523; P = 0) and HVPG (r = 0.34; P = 0.019). Glucagon significantly increases portal pressure [157][158][159] , and causes splanchnic vasodilation [148] . Geraghty et al [158] found a strong correlation between portal pressure and glucagon levels (r = 0.85).…”
Section: Angiogenesismentioning
confidence: 99%
“…It has been suggested that vasoconstriction is indirectly caused by an inhibited release of vasodilative pancreatic and gut peptides. Among insulin [15], VIP [16], substance P [17]and others, glucagon has a vasodilative effect on the mesenteric vascular bed and has been proposed as one regulator of mesenteric and portal blood flow [18, 19, 20]. The release of glucagon from the pancreatic α-cell is under the inhibitory control of somatostatin and its analogues [18, 21].…”
Section: Introductionmentioning
confidence: 99%
“…5,6 Other studies have shown an increased splanchnic production of carbon monoxide in portal hypertension 7 as well as an increased release of splanchnic vasodilatory peptides, such as glucagon. 8,9 Vasoconstrictor systems are also up-regulated, probably as a counter-regulatory response to the hyperdynamic state. 10 Sympathetic nervous and renin-angiotensin aldosterone systems are enhanced, and the plasma levels of vasopressin and endothelin-1 are elevated.…”
mentioning
confidence: 99%